Domestic and family violence, non‐lethal strangulation and social work intervention in the emergency department. (1st May 2020) - Marks, Jacqueline; Markwell, Alexandra; Randell, Thomas; Hughes, James
Abstract: Objective: To review domestic and family violence (DFV) and non‐lethal strangulation (NLS) presentations to an ED with 24‐h social work. Methods: Retrospective cohort study of 12 months of DFV presentations comparing demographics, perpetrator relationship, social work review, injuries and NLS incidence and assessment. Results: Women represent 90% of DFV presentations. In 26% of DFV presentations NLS was identified, with 47.5% clinically assessed appropriately. Social work did not review 34% of DFV presentations, 64% due to no referral. Conclusions: Social work referral for DFV is regularly missed despite 24‐h access. Assessment of NLS in ED requires improvement and standardised national guidelines.